The Effectiveness of Simulation and Role Play Technique to Teach Speaking for High and Low Motivation Students - Maria Agustin Daniastuti (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
Abstract: This study purposes is to find out the significance of motivation and teching learning technique effect toward students learning result score on speaking skill. this research was conducted at Tarciusius Vocational School Semarang and took thirty one students as data source. Experimental research was choosen to solve the research question with help of SPSS statistical prgram in order to increase the accuracy. This research were employed questionnaire, t-test, and f-test in data collection. Based on the finding, speaking skill learning result by using simulation technique and role play tend to achive better result on post-test than pre-test. Future testing shows that speaking skill learning result by using simulation technique significantly better than role play. Other findings show that high motivation studentssignificantly influence toward speaking learning result by using simulation technique and role play. In other hand Low motivation students does not significantly influence toward speaking skill learning result. Finally, this research conclude that simulation technique is appropriate learning technique in order to improve speaking learning result than role play.Keyword : Motivation, Simulation Technique, Role play